Cloning, sequencing and expression analysis of the equine hepcidin gene by real-time PCR - Oliveira Filho, Jose P. [UNESP]; Badial, Peres R. [UNESP]; Cunha, Paulo H. J. [UNESP]; Cruz, Tais F. [UNESP]; Araujo, Joao P. [UNESP]; Divers, Thomas J.; Winand, Nena J.; Borges, Alexandre Secorun [UNESP] (Elsevier B.V., 2010)
Equine serum or plasma iron concentration drops quickly during inflammation. Accumulation of iron inside macrophages and reduction of the intestinal absorption of this element cause hypoferremia during systemic inflammatory processes. These mechanisms are mediated by hepcidin, a 25 amino acids peptide synthesized mainly in the liver in response to iron stores and inflammation. Hepcidin is an important peptide for systemic iron homeostasis and also has antibacterial and antifungal activities. Hepcidin up-regulation is particularly useful during acute inflammation, especially before adaptive immunity occurs, restricting iron availability necessary for pathogenic microorganism growth. Hepcidin gene products have been previously characterized in man, non-human primates, rat, mouse, dog swine, cattle, fishes, reptiles and birds; but until now not in the horse. We have cloned and sequenced equine hepcidin mRNA and performed hepcidin expression analysis in different tissues collected from four healthy horses. The deduced precursor of equine hepcidin was most homologous to Bos taurus and Sus scrofa. The expressed profile of equine hepcidin in liver was very high. Expression in cervical spinal cord and cerebral cortex was much lower than liver but higher than lung, duodenum, stomach, spleen, kidney, skeletal muscle and bladder. This sequence will be helpful for additional studies on iron metabolism and inflammatory process in horses. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Equine; Hepcidin; mRNA expression; Inflammation; Innate immunity